Acne Therapy Across Time in the USA - Valeria De Bedout; Jonette Keri (European Medical Journal, 2019)
Acne vulgaris is the most common skin condition affecting the American population. The present review evaluates the topical and systemic therapies available in the USA for the management of acne reporting their relevance, efficacy, tolerability, and safety. This review also discusses alternative treatments such as light therapy, diet, and probiotics. Further research on acne therapy is needed given the high prevalence, and thus, the immense economic burden that the condition poses in our society.